Medicine and Health - o'g'li, Naimov Dilshod Qayim (Journal of Science in Medicine and Life, 2024)
We have received information about how and according to what principle medicine developed in the ancient civilization of Mesopotamia: each doctor, depending on his rating, had his own circle of patients. They paid him in direct proportion to the number of healthy clients. He was financially interested in ensuring that his charges were healthy. At that time, the causes of diseases were little studied. It was believed that illness was the work of God and it was forbidden to delve into it. Doctors devoted their attention and care to maintaining health and, in case of illness, prescribed natural remedies that strengthened the body and did not harm it, which we do not see today with drug treatment, when using artificial pills. The same system was observed in Greek civilization. We have reached records of Indian, Chinese, Tibetan and other methods of treating diseases with herbs and other natural products, which are still in great demand today.